A Microbial Functional Group‐Based CH4 Model Integrated Into a Terrestrial Ecosystem Model: Model Structure, Site‐Level Evaluation, and Sensitivity Analysis. (1st April 2020) - Song, Chaoqing; Luan, Junwei; Xu, Xiaofeng; Ma, Minna; Aurela, Mika; Lohila, Annalea; Mammarella, Ivan; Alekseychik, Pavel; Tuittila, Eeva‐Stiina; Gong, Wei; Chen, Xiuzhi; Meng, Xianhong; et al.
Abstract: Wetlands are one of the most important terrestrial ecosystems for land‐atmosphere CH4 exchange. A new process‐based, biophysical model to quantify CH4 emissions from natural wetlands was developed and integrated into a terrestrial ecosystem model (Integrated Biosphere Simulator). The new model represents a multisubstance system (CH4, O2, CO2, and H2 ) and describes CH4 production, oxidation, and three transport processes (diffusion, plant‐mediated transport, and ebullition). The new model uses several critical microbial mechanisms to represent the interaction of anaerobic fermenters and homoacetogens, hydrogenotrophic, and acetoclastic methanogens, and methanotrophs in CH4 production and oxidation. We applied the model to 24 different wetlands globally to compare the simulated CH4 emissions to observations and conducted a sensitivity analysis. The results indicated that (1) for most sites, the model was able to capture the magnitude and variation of observed CH4 emissions under varying environmental conditions; (2) the parameters that regulate dissolved organic carbon and acetate production, and acetoclastic methanogenesis had the significant impact on simulated CH4 emissions; (3) the representation of the process components of CH4 cycling showed that CH4 oxidation was about half or more of CH4 production, and plant‐mediated transport was the dominant pathway at most sites; and (4) the seasonality of simulated CH4 emissions can be controlled by soil temperature, water table position, or combinations thereof. Plain Language Summary: CH4 emission from wetlands is an important part of global carbon cycle. A new process‐based model was developed to quantify the CH4 emission from wetlands. The new model considered main microbial mechanisms and transport processes in wetland CH4 cycling, and the modeled results matched the observed CH4 emissions well at evaluation sites globally. A sensitivity analysis indicated the important role of parameters that controlled dissolved organic carbon and acetate production and acetoclastic methanogenesis. The assessment of process components of CH4 cycling demonstrated the importance of CH4 oxidation and plant‐mediated transport in wetland CH4 emission. Key Points: A new process‐based model incorporating microbial mechanisms was developed to quantify CH4 emissions from natural wetlands The model was applied to 24 different wetlands globally to compare the simulated CH4 emissions to observations The sensitivity analysis showed the significant impacts of parameters regulating DOC and acetate production, and acetoclastic methanogenesis on simulated CH4 emissions